CFH and CFHR structural variants in atypical Hemolytic Uremic Syndrome: Prevalence, genomic characterization and impact on outcome - Piras, Rossella; Valoti, Elisabetta; Alberti, Marta; Bresin, Elena; Mele, Caterina; Breno, Matteo; Liguori, Lucia; Donadelli, Roberta; Rigoldi, Miriam; Benigni, Ariela; Remuzzi, Giuseppe; Noris, Marina (Frontiers in Immunology, 2023)
Atypical hemolytic uremic syndrome (aHUS) is a rare disease that manifests with microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure, and is associated with dysregulation of the alternative complement pathway. The chromosomal region including CFH and CFHR1-5 is rich in repeated sequences, favoring genomic rearrangements that have been reported in several patients with aHUS. However, there are limited data on the prevalence of uncommon CFH-CFHR genomic rearrangements in aHUS and their impact on disease onset and outcomes. In this study, we report the results of CFH-CFHR Copy Number Variation (CNV) analysis and the characterization of resulting structural variants (SVs) in a large cohort of patients, including 258 patients with primary aHUS and 92 with secondary forms. We found uncommon SVs in 8% of patients with primary aHUS: 70% carried rearrangements involving CFH alone or CFH and CFHR (group A; n=14), while 30% exhibited rearrangements including only CFHRs (group B; n=6). In group A, 6 patients presented CFH::CFHR1 hybrid genes, 7 patients carried duplications in the CFH-CFHR region that resulted either in the substitution of the last CFHR1 exon(s) with those of CFH (CFHR1::CFH reverse hybrid gene) or in an internal CFH duplication. In group A, the large majority of aHUS acute episodes not treated with eculizumab (12/13) resulted in chronic ESRD; in contrast, anti-complement therapy induced remission in 4/4 acute episodes. aHUS relapse occurred in 6/7 grafts without eculizumab prophylaxis and in 0/3 grafts with eculizumab prophylaxis. In group B, 5 subjects had the CFHR31-5::CFHR410 hybrid gene and one had 4 copies of CFHR1 and CFHR4. Compared with group A, patients in group B exhibited a higher prevalence of additional complement abnormalities and earlier disease onset. However, 4/6 patients in this group underwent complete remission without eculizumab treatment. In secondary forms we identified uncommon SVs in 2 out of 92 patients: the CFHR31-5::CFHR410 hybrid and a new internal duplication of CFH. In conclusion, these data highlight that uncommon CFH-CFHR SVs are frequent in primary aHUS and quite rare in secondary forms. Notably, genomic rearrangements involving the CFH are associated with a poor prognosis but carriers respond to anti-complement therapy.